Novel hosts can incur fitness costs to a frugivorous insect pest. Issue 4 (19th April 2022) - Lampasona, Timothy; Rodriguez‐Saona, Cesar; Nielsen, Anne L.
Abstract: In phytophagous insects, adult attraction and oviposition preference for a host plant are often positively correlated with their immature fitness; however, little is known how this preference–performance relationship changes within insect populations utilizing different host plants. Here, we investigated differences in the preference and performance of two populations of a native North American frugivorous insect pest, the plum curculio ( Conotrachelus nenuphar )—one that utilizes peaches and another that utilizes blueberries as hosts—in the Mid‐Atlantic United States. We collected C .  nenuphar adult populations from peach and blueberry farms and found that they exhibited a clear preference for the odors of, as well as an ovipositional preference for, the hosts they were collected from, laying 67%–83% of their eggs in their respective collected hosts. To measure C .  nenuphar larval performance, a fitness index was calculated using data on larval weights, development, and survival rate from egg to 4th instars when reared on the parent's collected and novel hosts. Larvae of C .  nenuphar adults collected from peach had high fitness on peach but low fitness when reared on blueberry. In contrast, larvae from C .  nenuphar adults collected in blueberry had high fitness regardless of the host on which they were reared. In this study, we show that utilizing a novel host such as blueberry incurs a fitness cost for C .  nenuphar from peaches, but this cost was not observed for C .  nenuphar from blueberries, indicating that the preference–performance relationship is present in the case of insects reared on peach, but insects reared on blueberry were more flexible and able to utilize either host, despite preferring blueberry. Abstract : In this study, we use a series of experiments to test whether Conotrachelus nenuphar 's behavior conforms to the preference–performance hypothesis (PPH). Using insects from two hosts, peach and blueberry, we tested olfactory host preference, oviposition choice, and larval fitness between both hosts. We found that C. nenuphar that use peach are not able to successfully use blueberry, but C. nenuphar that use blueberry are able to use peach, and that choice and attraction are consistent with PPH assumptions.